A rare case of bacteremia caused by Propionibacterium (Propionimicrobium) lymphophilum. (April 2020) - Cobo, Fernando; Gómez, Esther; Rodríguez-Granger, Javier; Sampedro, Antonio; García-Salcedo, José A.; Navarro-Marí, José María
Abstract: Propionibacterium (Propionimicrobium) lymphophilum is a Gram-positive anaerobic rod involved in few human diseases. We report a rare case of bacteremia due to this microorganism in an elderly patient. A 95-year-old woman without a remarkable medical history presented with dyspnea, chest pain and fever for seven days. Blood cultures resulted in isolation of P. lymphophilum . Resistance only to metronidazole was found. Treatment with amoxicillin-clavulanic acid was established, and the patient was discharged and improvement of her general condition was documented. Highlights: Propionimicrobium lymphophilum is rarely associated with human infections. This is the first case of bacteremia caused by this pathogen in pure culture. Mass spectrometry software should be constantly updated. The strain, as well as in other published cases, was resistant to metronidazole.